THE ROLE OF THE WESTERN CASPIAN TRADING CENTERS IN THE DEVELOPMENT OF TRADE BETWEEN DERBENT AND RUSSIA (IN THE 17TH -18TH CENTURIES) - Magomedov, N A; Magaramov, S A (History, Archeology and Ethnography of the Caucasus, 2016)
The article covers trading relations between Derbent and other trading centers of the Western Caspian Sea region and their role in maintaining of trade ties between Russia and Derbent. Basing on available written sources, the authors of the article describe trade routes along the western coast of the Caspian Sea, as well as shipping trade lanes. The authors present numerical data on the land and maritime trade in the region, analyze a range of goods and development of trade infrastructure.
Keywords: Western Caspian Sea region; Derbent; trading centers; regional trade; eastern merchants